2019
DOI: 10.1248/bpb.b19-00249
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bile Acid Concentrations after Administration of Ketoconazole or Rifampicin to Chimeric Mice with Humanized Liver

Abstract: Drug-induced liver injury (DILI) is a common side effect of several medications and is considered a major factor responsible for the discontinuation of drugs during their development. Cholestasis is a DILI that results from impairment of bile acid transporters, such as the bile salt export pump (BSEP), leading to accumulation of bile acids. Both in vitro and in vivo studies are required to predict the risk of drug-induced cholestasis. In the present study, we used chimeric mice with humanized liver as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies have reported minor elevations in ALT or bile acid in response to IDILI drugs in mice with humanized livers, suggesting that this model is sufficient to replicate the early steps that proceed an adaptive immune attack and more significant liver injury. , A particularly impressive humanized liver model is derived from the NOG mouse expressing a thymidine kinase transgene (TK-NOG). A recent study in TK-NOG mice demonstrated both a humanized profile of biliary excretion as well as cholestatic liver injury after 1 week of treatment with bosentan .…”
Section: Investigative Toolsmentioning
confidence: 99%
“…Several studies have reported minor elevations in ALT or bile acid in response to IDILI drugs in mice with humanized livers, suggesting that this model is sufficient to replicate the early steps that proceed an adaptive immune attack and more significant liver injury. , A particularly impressive humanized liver model is derived from the NOG mouse expressing a thymidine kinase transgene (TK-NOG). A recent study in TK-NOG mice demonstrated both a humanized profile of biliary excretion as well as cholestatic liver injury after 1 week of treatment with bosentan .…”
Section: Investigative Toolsmentioning
confidence: 99%
“…The reason for the increase in ALT activity is also correlated with skeletal muscle, cardiac injury or metabolic state, except for histopathology change (Zhao et al, 2017). Moreover, a previous study found that the levels of hepatic and serum BAs and BA-related genes increase notably, with no elevation in serum ALT, AST, and alkaline phosphatase levels after administering a dose of RIF (Sanoh et al, 2019). Another study showed that the levels of serum conjugated BAs [glycocholic acid (GCA) and taurocholic acid (TCA)] increase in the rats with bile duct hyperplasia without significant changes in ALT and AST levels (Slopianka et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Cholesterol 7α hydroxylase (CYP7A1) is a rate-limiting enzyme in bile acid synthesis in hepatocytes. Its activity is regulated by the negative feedback of the farnesoid X receptor/small heterodimer partner (FXR/SHP) pathway ( Sanoh et al, 2019 ). There was evidence ( Xu et al, 2016 ) that RFP suppresses the FXR/SHP pathway, increases CYP7A1 mRNA expression, and promotes bile acid synthesis in hepatocytes.…”
Section: Molecular Mechanisms Of Rifampicin-induced Liver Injurymentioning
confidence: 99%